Relationship between Nutritional Status and Flat Foot in Children - Joyce Phua Pau Fung; Yoyos Dias Ismiarto; Wulan Mayasari (Faculty of Medicine Universitas Padjadjaran, 2017)
Background: Pediatric flatfoot has been reported as the highest clinical complains for foot problems in pediatric department. Nutritional status has showed great influence on the occurrence of flat foot. There are many debates regarding whether underweight or overweight children are more prone to flatfoot. The aim of this study was to analyze the relationship between nutritional status and flatfoot in children.Methods: A cross sectional study was conducted from July to October 2015 in 3 primary schools in Kecamatan Jatinangor. There were 259 children of grade 4 to 5 included in this study. Flatfoot screening was based on measurement of footprint and calculation using Chippaux-smirak index (CSI). The height and weight of children were measured to obtain their Body Mass Index (BMI). Nutritional status was classified based on CDC BMI-for-age growth charts. Analysis was done using chi-square test.Results: There was significant association between nutritional status and flatfoot with p value<0.001.The prevalence of flatfoot in children grade 4to5is40%. When compared to the normal weight children, the overweight children showed prevalence ratio of 1.97(95% CI:1.47 to 2.64) while the underweight children showed prevalence ratio of 1.34 (95% CI:1.78 to 2.25).This stated that the risk of developing flat foot was higher in overweight children.Conclusions: There is significant association between nutritional status with children grade4 to 5. Overweight children are more prone to flat foot. [AMJ.2017;4(1):152–6] DOI: 10.15850/amj.v4n1.1038